Determinan Preferensi Penduduk untuk Tidak Memiliki Jaminan Kesehatan: Studi Kasus di Kabupaten Lima Puluh Kota, Provinsi Sumatera Barat - Saputra, Dio Dwi (Politeknik Statistika STIS, 2025)
Health insurance is one of the efforts to achieve the Sustainable Development Goals target, namely Universal Health Coverage. Based on data from Statistics Indonesia, almost a quarter of Indonesia’s population still does not have health insurance. One of the regency/municipalities with a fairly high percentage of population who do not have health insurance is Lima Puluh Kota Regency. This research aims to determine the characteristics of Lima Puluh Kota regency population who do not have health insurance and how this influences their preferences for owning health insurance. By using descriptive analysis and binary logistic regression, it was found that the characteristics of Lima Puluh Kota Regency who prefer no to have health insurance are living in urban areas, their economic status is not poor, never married/divorced, age group 0 – 9 years old (children), not working, not using the internet, have health complaints and the highest level of education is Primary or Secondary school. Therefore, it is hoped that the government can make policies that are right on target by specifically intervening in the promotion of health insurance ownership based on these characteristics. Collaboration with private health insurance providers can also expand the scope of health insurance ownership.